Museum of papermaking in Duszniki-Zdrój as an initiator of serial nomination of the most precious European paper mills for the UNESCO list - Szymczyk, Maciej (Protection of Cultural Heritage, 2019)
The paper mill in Duszniki-Zdrój was established before 1562. Thanks to the profitability of production, over the centuries it was extended and decorated in the style of a manor house. Since 1968, it has been the seat of the Museum of Papermaking. In recent years, awareness of the historical value of the mill has increased. Thanks to the efforts of the museum, in 2011 the mill was granted the status of a Monument of History, and in the following years, efforts were made to include it in the UNESCO list. The concept of serial nomination of the most valuable paper mills in Europe serves to increase the chances of gaining an entry. The Polish museum is the coordinator of this project. So far, agreements have been signed on joint nomination efforts with the paper mills in Velké Losiny in the Czech Republic and Homburg (district Triefenstein) in Germany, and talks are being held with the paper mill in Ambert in France. Currently, in cooperation with Professor Bogusław Szmygin, the museum is working on a comparative analysis of all the preserved paper mills, which will allow to select 2-3 more partners.